Patient-centered Care’s Relationship with Substance Use Disorder Treatment Utilization - Park, Sunggeun (Ethan) (J Subst Abuse Treat, 2020)
BACKGROUND: Calls for more patient-centered care are growing in the substance use disorder (SUD) treatment field. However, evidence is sparse regarding whether patient-centered care improves access to, or utilization of, effective treatment services. METHODS: Using nationally representative survey data from SUD treatment clinics in the United States, we examine the association between patient-centered clinical care and the utilization of six services: methadone, buprenorphine, behavioral treatment, routine medical care, HIV testing, and suicide prevention counseling. We measured clinics’ practice of and emphasis on patient-centered care with two variables: (1) whether the clinic regularly invites patients into clinical decision-making processes, and (2) whether supervisors believe in patient-centered healthcare and shared decision-making practices within their clinics. RESULTS: In 2017, only 23% of SUD treatment clinics regularly invited patients into care decision-making meetings when their cases were discussed. A composite variable captured clinical supervisors’ own experience with and expectations for patient-clinician interaction within their clinics (Cronbach’s alpha=0.79). Results from regression models that controlled for several organizational and environmental factors show that patient-centered care was independently associated with greater utilization of four of six evidence-based services. CONCLUSIONS: A minority of SUD clinics practice patient-centered healthcare in the United States. Given the connection to evidence-based services, increasing participatory mechanisms in SUD treatment service provision can facilitate patients’ access to appropriate and evidence-based services.